2000
DOI: 10.1116/1.582271
|View full text |Cite
|
Sign up to set email alerts
|

Mass-resolved ion energy distributions in continuous dual mode microwave/radio frequency plasmas in argon and nitrogen

Abstract: The control of plasma-surface interactions in terms of synergistic effects of ions, photons, and chemically active species is important for the optimization of plasma enhanced chemical vapor deposition of thin films and for plasma-induced surface modification. In the present work, we use a dual-mode microwave/radio frequency (MW/rf) plasma system, in which we investigate the effect of plasma parameters (gas type and pressure, self-bias voltage, for example) on the energy and flux of ionic species arriving at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…Some examples are: Heim and Stori [63], Hallil et al [64], Gans et al [65], Babkina et al [61], and Schiesko et al [32]. In general, one expects the average energies of the ions in the discharge source to be a few eV as determined by the ambipolar field generated by the electrons.…”
Section: Other Experimentsmentioning
confidence: 99%
“…Some examples are: Heim and Stori [63], Hallil et al [64], Gans et al [65], Babkina et al [61], and Schiesko et al [32]. In general, one expects the average energies of the ions in the discharge source to be a few eV as determined by the ambipolar field generated by the electrons.…”
Section: Other Experimentsmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the plasma properties in a low‐pressure microwave discharge (such as ECR) in combination with r.f. bias to ensure these conditions . A suitable experimental method fulfilling this requirement is the mass spectrometry of neutral molecules and radicals, so‐called Neutral Mass Spectrometry (NMS), and also the Energy‐Resolved Mass Spectrometry (ERMS) .…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, ERMS allows determining of other parameters important for the deposition of DLC films: the composition of the ion flux and its energy. Using mass spectrometry of the methane discharge in ECR/RF, some authors investigated various processes of the formation and changes of the plasma discharge and the distribution of the ionic energy in methane/argon and methane/nitrogen mixtures . The mobility of ions in the methane/argon discharge has been also investigated…”
Section: Introductionmentioning
confidence: 99%
“…Hallil et al [5] proposed an investigation on the study of a dual-mode microwave/radio frequency plasma system. They reported that Ar + , N 2 + and N 1 + ions show structured Ion Electron Distribution Functions (IEDF) at the rf-powered electrode.…”
Section: Introductionmentioning
confidence: 99%